Netralitas Netralitas Perangkat Desa Dalam Pilkada Serentak Tahun 2024 Di Kabupaten Bantul - Bintang Ashara Bela; Dian Eka Rahmawati (ARISTO, 2026)
The neutrality of village apparatus is an imperative obligation that must be upheld without compromise. This study aims to analyze the neutrality of village apparatus during the simultaneous regional elections (Pilkada) in 2024 in Bantul Regency. A qualitative approach was employed, with data collected through interviews and documentation studies. The findings reveal several violations committed by village officials that contradict the principle of neutrality. The causes of this lack of neutrality are influenced by several factors, including cultural influences, political ambition, kinship or familial ties, and local political pressures. In Javanese culture, the concept of "ewuh pekewuh," which refers to a feeling of hesitation or reluctance out of respect or social obligation, reflects a cultural aspect that weakens the application of neutrality values. Political ambition often impacts the neutrality of village apparatus, as political positions are considered strategic for accelerating career advancement. Political rewards or promises extend beyond positions to include beneficial programs for involved parties. Local political pressure examples include coercion from party elites at the district level directed toward village apparatus. Furthermore, the most emphasized factor is kinship or familial relationships, which can disrupt the professionalism of the electoral system and the neutrality of village officials.